The Implementation of Problem Based Learning to Improve The Students’ Learning Outcomes of Cognitive Aspects in Oxy Acetylene Welding Course - Bernardus Agus Munadi (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
This study aims to improve the learning outcomes of cognitive aspects among X grade students of Metal Fabrication Engineering and Manufacturing, Vocational High School (VHS) using Problem-Based Learning (PBL) method. This study used classroom action research, which was conducted in two cycles. Each cycle consisted of four stages, i.e. planning, implementation, observation, and reflection. This study involved one collaborator to assist researchers in implementing PBL and to monitor the learning process. The data collection technique used observation method with checklist and rating scale instrument. The data were analyzed descriptively. The reserach results showed that the implementation of PBL method in ignition system learning improve the students’ learning activities with the percentage of 11.20%, the learning activities, in which 29 students was in very high category and 3 students with high category. Also, the learning outcomes of cognitive aspects getting higher amounted to 5.32% consisting of remembering (86.87%), understanding (77.68%), applying (78.77%), analyzing (79.61%), evaluation (77.97%), and creating (79.16%) respectively. Moreover, the students’ learning outcomes rised of which 29 students (91.31%) achieved above the minimum completeness criteria. Keywords: problem-based learning, cognitive aspects, learning outcomes